Cannabis use and heart transplant listing: A survey of clinician practices. - Onyedika J Ilonze; Shannon M Knapp; Yelena Chernyak; Robert L Page; LaKeisha J Boyd; Sula Mazimba; Subha V Raman; Chioma O Enyi; Larry A Allen; Khadijah Breathett (PLoS ONE)
No consensus exists for heart transplant listing for patients who use cannabis. We conducted a web-based survey to assess knowledge, and practice patterns towards patients with heart failure who use cannabis referred for transplant. A total of 140 clinicians (cardiologists (41.4%, n = 58), surgeons (7.1%, n = 10), pharmacists (9.3%, n = 13), advanced practice providers and coordinators) responded and responses were grouped by whether they responded that cannabis is "illegal in my state" (illegal), or "legal for medical and recreational use in my state," (legal). There was a statistically significant difference in responses between the groups in the frequency of cannabis use that should preclude a patient from HT listing p = 0.0330) with respondents where cannabis is legal tending to answer that higher frequencies were acceptable. The groups in the "legal group" responded that a validated cannabis screening questionnaire could evaluate HT eligibility (p = 0.0111). A majority in the illegal group responding "No" as to whether their program allows pre- or post-transplant patients to use prescribed cannabis products (p < 0.0001). A majority in the illegal group responding "No" while the majority in the legal group responded "Yes" to "Does your HT center's current selection criteria policy address medical cannabis use in potential transplant candidates?" (p = 0.0001). Health care providers generally agreed that a validated cannabis use disorder screening questionnaire would be useful and that 6 months of abstinence from cannabis is sufficient prior to HT listing. Significant heterogeneity exists regarding cannabis use as it relates to heart transplantation.